Pemanfaatan Briket Arang Tempurung Kelapa Sebagai Sumber Energi Alternatif - Esmar Budi (Bahasa Indonesia, 2017)
ABSTRACT: The use of charcoal briquettes contributes to the reduction of dependence on petroleum and gas fuels, especially for small urban communities while at the same time supporting the utilization of coconut shell waste as fuel. Consumption of coconut (cocos nucifera), especially as a coconut milk in Jakarta is large enough to contribute to produce coconut shell waste in the market. Generally, coconut shell waste has been used as charcoal fuel. However, the formation of coconut shell charcoal briquettes provides advantages over charcoal such as not smoky, clean and easy to pack. Furthermore, the utilization of coconut shell charcoal briquette is in line with the solution of current global problems related to pollution (pollution), alternative energy and environmentally friendly technologies. Therefore, the increased understanding and awareness through the use of briquettes, especially for the small urban community through training the formation and use of coconut shell charcoal briquettes as fuel need to be done so that the function and its objectives are achieved. The training was conducted with the number of participants of approximately 20 people also involve students as the spearhead in providing understanding and awareness using the workshop facility of coconut shell charcoal briquette's formation at FMIPA Universitas Negeri Jakarta. The training includes the formation of coconut shell charcoal briquettes from coconut shell removal, burning (pyrolysis), grinding to printing and drying (drying). Then tested the use of briquettes for cooking water. ABSTRAK: Penggunaan briket arang tempurung memberikan kontribusi pada pengurangan ketergantungan pada bahan bakar minyak dan gas khususnya bagi masyarakat kecil di perkotaan dan pada saat yang bersamaan mendukung pemanfaatan sampah tempurung kelapa sebagai bahan bakar. Konsumsi buah kelapa (cocos nucifera) tua khususnya sebagai santan di Jakarta cukup besar sehingga turut andil dalam menghasilkan sampah tempurung kelapa di pasar. Umumnya sampah tempurung kelapa telah dimanfaatkan sebagai arang bahan bakar. Namun demikian pembentukan briket arang tempurung kelapa memberikan kelebihan dibandingkan arang seperti tidak berasap, bersih dan mudah kemas. Lebih jauh pemanfaatan briket arang tempurung kelapa sejalan dengan penyelesaian permasalahan global saat ini yang berkaitan dengan polusi (pencemaran), energi alternatif dan teknologi yang ramah lingkungan. Untuk itu peningkatan pemahaman dan kesadaran akan penggunaan briket khususnya bagi masyarakat kecil perkotaan melalui pelatihan pembentukan dan penggunaan briket arang tempurung kelapa sebagai bahan bakar perlu dilakukan agar fungsi dan tujuannya tercapai. Pelatihan yang dilaksanakan dengan jumlah peserta kurang lebih 20 orang juga melibatkan mahasiswa sebagai ujung tombak dalam memberikan pemahaman dan kesadaran tersebut dengan menggunakan fasilitas bengkel pembentukan briket arang tempurung kelapa di FMIPA Universitas Negeri Jakarta. Pelatihan meliputi proses pembentukan briket arang tempurung kelapa mulai dari pembersihan tempurung kelapa, pembakaran (pirolisis), penggilingan hingga pencetakan dan penjemuran (pengeringan). Kemudian dilakukan uji coba pemakaian briket untuk memasak air.Kata Kunci: arang tempurung kelapa, briket, pirolisis, pembakaran.